PERSEPEKTIF SOSIOLOGI-KOMUNIKASI PENERAPAN QONUN-QONUN LARANGAN MEMBAWA HANDPHONE PADA SANTRI PESANTREN MAMBA’UL HUDA - Maskur Maskur; Moh. Yuafi (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
The application of qanuns in a pesantren basically does not take place in a vacuum, but in a space of social interaction, which is full of dynamics of communication. This article wants to examine how the sociological-communication side of the implementation of the qonun prohibits carrying cellphones at the Mamba'ul Huda Islamic boarding school. The results showed that the prohibition on carrying cellphones was the result of the many negligence committed by the students when they brought cellphones, even though the administrators had often been reminded to carry out their obligations.